The communicative and linguodidactic potential of epistolary texts: an applied aspect (based on the material of D. A. Mongush — A. S. Amanzholov’s mail correspondence) - Amanzholova, Jemma B.; Iskendir, Akkuralay A.; Shaimerdenova, Nursulu Zh. (The New Research of Tuva, 2024)
The article analyzes the communicative potential of epistolary texts and their prospects for linguodidactics — Russian and Kazakh. The material consists of fragments of private correspondence (1957–1984) by the Tuvan scholar — philologist D. A. Mongush addressed to his Kazakh colleague A. S. Amanzholov. The contents of seven documents are presented in detail, including two letters, four postcards with descriptions of envelopes and front and back sides, and one telegram. These texts are being introduced to scientific circulation for the first time. The article also substantiates the concept of an “elite bilingual personality” and argues in favor of classifying their Russian-language texts as authentic. It rationalizes the approach to teaching Russian language and training future teachers of Russian in the bilingual Kazakh-Russian communicative bilingual situation of Kazakhstan, as it does not disregard the traditional approach but expands linguistic and didactic tools. A. Mongush’s letters to A. S. Amanzholov can be used as examples of the epistolary genre in practical school classes and for further research in university audiences. They can also help to expand previously unknown knowledge about the history of Turkology.